2020
DOI: 10.7554/elife.57572
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily distant I domains can functionally replace the essential ligand-binding domain of Plasmodium TRAP

Abstract: Inserted (I) domains function as ligand-binding domains in adhesins that support cell adhesion and migration in many eukaryotic phyla. These adhesins include integrin αβ heterodimers in metazoans and single subunit transmembrane proteins in apicomplexans such as TRAP in Plasmodium and MIC2 in Toxoplasma. Here we show that the I domain of TRAP is essential for sporozoite gliding motility, mosquito salivary gland invasion and mouse infection. Its replacement with the I domain from Toxoplasma MIC2 fully r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 56 publications
3
60
1
Order By: Relevance
“…This could suggest that the major surface protein CSP mediates low affinity unspecific binding to a surface with adhesins of the TRAP family providing for stronger but transient substrate adhesion (18,35,41,42,48). Clearly, modulation of adhesion and deadhesion cycles plays a complex role in motility and invasion.…”
Section: Sporozoites Only Move On Stiffer Substratesa Mechanism For Amentioning
confidence: 99%
See 1 more Smart Citation
“…This could suggest that the major surface protein CSP mediates low affinity unspecific binding to a surface with adhesins of the TRAP family providing for stronger but transient substrate adhesion (18,35,41,42,48). Clearly, modulation of adhesion and deadhesion cycles plays a complex role in motility and invasion.…”
Section: Sporozoites Only Move On Stiffer Substratesa Mechanism For Amentioning
confidence: 99%
“…Several sporozoite proteins have been found to be important for salivary gland invasion (16). Whether there is a specific receptor mediating tissue-specific invasion of salivary glands is currently under debate (17,18). Liver invasion is thought to be triggered by highly sulphated heparan sulphate proteoglycans which protrude through fenestrations of endothelial cells lining the liver sinusoids (14,19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Typical back-and-forth movement termed patch-gliding (Münter et al, 2009) of hemolymph sporozoites was most frequently observed in GFP-GPI and SP-GFP-CSP_add parasites, while R-GFP-CSP sporozoites were gliding in the most robust manner. With over 20% gliding midgut sporozoites this reached the levels of hemolymph sporozoites (Münter et al, 2009; Klug et al, 2020). Over 10% of TSR-GFP-CSP sporozoites were also gliding.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, proteins containing adhesive domains like TRAPs allow the parasite to interact with receptors present at the host cell surface and are linked to the glideosome, a molecular machine necessary for parasite motility and host cell invasion (3). The importance of adhesive domains was demonstrated in recent studies on Plasmodium berghei TRAP in which deletion of the vWFA domain abolished gliding motility, mosquito salivary gland invasion and mouse infection (24). For these reasons, these proteins could be important targets for immunological or chemotherapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…This conservation exceeds the Babesia genus as re ected by the good tting of the predicted BbiTRAP-1 3D structure with the Sporozoite surface protein 2 of P. vivax, con rming the functional importance of this protein in critical processes not only in the Babesia genus, but also among other apicomplexan parasites. Conserved domains like the vWFA with similar overall structures in distant phyla were reported to be polyspeci c in Apicomplexa giving the parasites the versatility to interact with multiple ligands and migrate into diverse organs (24).…”
Section: Discussionmentioning
confidence: 99%